Let
P
=
2
0
0
8
2
0
0
7
−
2
0
0
8
and
Q
=
2
0
0
8
2
+
2
0
0
9
.
What is the
remainder
when
P
is divided by
Q
?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
notice that P is in the form x 2 0 0 7 -x and Q is in the form x 2 +x+1
let f(x)= x 2 0 0 7 -x g(x)= x 2 +x+1
f(x)=g(x)*q(x)+R
Let g(x) be 0.
Then f(x)=R
x 2 +x+1=0
x 3 =1
putting the value in f(x)
f(x)= x 2 +2 =2008*2008+2 =4032066
R=4032066
using multiple subtractions , notice that a mod b = (a-b) mod b finally got the answer ^_^ , great problems
Problem Loading...
Note Loading...
Set Loading...
Let R and S be the next polinomials:
R ( x ) = x ( x 2 0 0 6 − 1 ) S ( x ) = x 2 + x + 1
We use this polinomials to solve this problem: P = 2 0 0 8 2 0 0 7 − 2 0 0 8 = 2 0 0 8 ⋅ ( 2 0 0 8 2 0 0 6 − 1 ) so P = R ( 2 0 0 8 ) Q = 2 0 0 8 2 + 2 0 0 9 = 2 0 0 8 2 + 2 0 0 8 + 1 so Q = S ( 2 0 0 8 )
We know that for every natural number n ,
x n − 1 = ( x − 1 ) ⋅ ( x n − 1 + x n − 2 + ⋯ + x 2 + x + 1 )
Applying this relation to R ( x ) we have,
R ( X ) = x ⋅ ( x − 1 ) ⋅ ( x 2 0 0 5 + x 2 0 0 4 + ⋯ + x 2 + x + 1 ) = ( x − 1 ) ⋅ ( x 2 0 0 6 + x 2 0 0 5 + ⋯ + x 3 + x 2 + x ) = ( x − 1 ) ⋅ [ ( x 2 0 0 4 + x 2 0 0 1 + ⋯ + x 6 + x 3 + 1 ) ⋅ ( x 2 + x + 1 ) − 1 ] ≡ ( 1 − x ) ( m o d S ( x ) ) ≡ ( x 2 + 2 ) ( m o d S ( x ) )
Then
P = R ( 2 0 0 8 ) ≡ ( 2 0 0 8 2 + 2 ) ( m o d S ( 2 0 0 8 ) ) ≡ 4 0 3 2 0 6 6 ( m o d Q )
So, the answer is 4 0 3 2 0 6 6